2023
DOI: 10.2478/eujss-2023-0009
|View full text |Cite
|
Sign up to set email alerts
|

Population’s Mental Health after Wave V of COVID in a Disadvantaged Region of North-Hungary

Abstract: We examined the level of stress, aggression, health anxiety and well-being and their changes in almost every wave of the pandemic, and we have reported about the results in national and international studies. In Wave V, the prolonged effect of the pandemic, and, over the mental situational picture, the population’s post-traumatic condition was also examined. Our current research is focusing on the situational picture of North-Hungary, our aim is to get know the mental state of the region’s population. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…During the study series, we monitored and followed the changes of the levels of stress, health anxiety, aggression, hope and mental well-being in the second, third, fourth and fifth waves of the pandemic. Our results have been reported in different national and international studies in which the population's mental health is shown to be below the average [4,11,12].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…During the study series, we monitored and followed the changes of the levels of stress, health anxiety, aggression, hope and mental well-being in the second, third, fourth and fifth waves of the pandemic. Our results have been reported in different national and international studies in which the population's mental health is shown to be below the average [4,11,12].…”
Section: Introductionsupporting
confidence: 79%
“…The COVID-19 pandemic posed such a medical, economic, physical and mental hygienic challenge to the humanity that it caused severe damage in terms of people's mental health and well-being [1][2][3]. The changed living conditions were associated with the worsening of the symptoms of depression, perceived stress and anxiety, and the exacerbation of using psychoactive drugs worldwide [4][5][6]. It has also become obvious by now that the passing of acute danger, the end of the pandemic, has not meant the return to the economic, social and mental situation prior the pandemic, as the damages in the physical, mental and social life are still present among the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation